Inclusive Design Studios: Rethinking the Instructor’s Role - Pilat, Stephanie Z; Person, Angela (Enquiry The ARCC Journal for Architectural Research, 2022)
The culture of the architectural design studio continues, in large part, to be based on centuries old traditions. Research on teaching, learning and bias suggest, however, that a rethinking of these traditions is long overdue if we aim to create inclusive learning environments and diversify our profession. Drawing on recent research on the cultivation of expertise, student motivation and stereotype threat, this essay considers how we might rethink design studio instruction. Studies on the development of expertise suggest a critical re-imagining of the instructor’s role in design studios. Research on student motivation suggests that many of the traditional practices of architectural education inevitably leave students unmotivated and need to be reconsidered. Finally, research on the ways in which stereotypes impact academic performance illuminate some of the roadblocks to diversifying our classrooms and profession. This essay shares evidence-based strategies to address these roadblocks and traditions to develop a more inclusive and effective design studio culture.